Endogenous hydrogen sulfide improves vascular remodeling through PPARδ/SOCS3 signaling - Tian, Danyang (J Adv Res, 2020)
INTRODUCTION: Mounting evidences demonstrated the deficiency of hydrogen sulfide (H(2)S) facilitated the progression of cardiovascular diseases. However, the exact effects of H(2)S on vascular remodeling are not consistent. OBJECTIVES: This study aimed to investigate the beneficial role of endogenous H(2)S on vascular remodeling. METHODS: CSE inhibitor, DL-propargylglycine (PPG) was used to treat mice and vascular smooth muscle cells (VSMCs). Sodium hydrosulfide (NaHS) was given to provide hydrogen sulfide. Vascular tension, H&E staining, masson trichrome staining, western blot and CCK8 were used to determine the vascular remodeling, expressions of inflammatory molecules and proliferation of VSMCs. RESULTS: The deficiency of endogenous H(2)S generated vascular remodeling with aggravated active and passive contraction, thicken aortic walls, collagen deposition, increased phosphorylation of STAT3, decreased production of PPARδ and SOCS3 in aortas, which were reversed by NaHS. PPG inhibited expression of PPARδ and SOCS3, stimulated the phosphorylation of STAT3, increased inflammatory molecules production and proliferation rate of VSMCs which could all be corrected by NaHS supply. PPARδ agonist GW501516 offered protections similar to NaHS in PPG treated VSMCs. Aggravated active and passive contraction in PPG mice aortas, upregulated p-STAT3 and inflammatory molecules, downregulated SOCS3 and phenotype transformation in PPG treated VSMCs could be corrected by PPARδ agonist GW501516 treatment. On the contrary, PPARδ antagonist GSK0660 exhibited opposite effects on vascular contraction in aortas, expressions of p-STAT3 and SOCS3 in VSMCs compared with GW501516. CONCLUSION: In a word, endogenous H(2)S protected against vascular remodeling through preserving PPARδ/SOCS3 anti-inflammatory signaling pathway. Deficiency of endogenous H(2)S should be considered as a risk factor for VSMCs dysfunction